Вплив анiзотропiї обмiнної взаємодiї гейзенберга на процес намагнiчення фрустрованого ромбiчного ланцюжка у сильному магнiтному полi - Krupnitska, O. M. (Publishing house "Academperiodika", 2019)
A frustrated diamond spin chain in a z- or x-aligned external magnetic field has been considered in the framework of the spin-1/2 antiferromagnetic XXZ Heisenberg model. The magnetization process of the frustrated diamond spin chain is analyzed, by using the effective models found in the strong-coupling approximation in the case where the Heisenberg interaction anisotropy parameter Δ > 1. The theory is applied to explain experimental data for natural mineral azurite, Cu3(CO3)2(OH)2.